Microbial reduction of nitrous oxide at low pH - Almloff, Marc Jordan (Kansas State University, 2023)
Nitrous oxide (N₂O) is a potent greenhouse gas and an ozone-depleting substance. Its main emission comes from soil microorganisms in agricultural sectors. Recently, the diversity of the nosZ gene encoding for nitrous oxide reductase (NosZ) catalyzing the conversion of N₂O to N₂ was found to be much broader than expected. The microorganisms that possess nosZ split into two clades that follow denitrifying (clade I) and non-denitrifying (clade II) bacteria. With the unexpected diversity of bacteria possessing nosZ, environments that are not ideal for denitrifiers may be habitable for other microorganisms. Low pH environments are known to inhibit denitrification, especially the conversion of N₂O to N₂ starting at pH 6.8, resulting in N₂O accumulation. Impacts for these microorganisms include silage which has recently been shown to emit the third highest quantity of N₂O in the agricultural sector. The fermentation process within silage reduces the pH to 4-5 inhibiting the conversion of N₂O to N₂. The goal of this research is to develop an inoculum that can be used in silage to mitigate N₂O emissions at low pH. It is essential to learn how pH affects nosZ and how the bacteria may be able to protect against acidity. Samples from agricultural fields and activated sludge were used to gradually enrich the microorganisms to lower pH values at 0.5-unit increments, starting from pH 7 to pH 5. Results showed that the enrichment cultures reduced N₂O at pH as low as 5.5, but not at pH 5. At the end of each enrichment period at different pH values, the Michaelis-Menten analysis and the metagenomic analysis were performed. Clade II bacteria were more dominant than clade I bacteria at all conditions, however, clade I microorganisms increased in relative abundance over the decrease in pH. Michaelis-Menten showed that the affinity of bacteria at pH 7 is greater than that of bacteria at pH 5.5, which can be confirmed with the observed reduction rates of N₂O. Due to the wide taxa range of clade II nosZ, kinetics and metagenomic data cannot be conclusive since only clade II A and clade II B primers were analyzed. Further experiments are needed to understand the kinetics of the microorganisms at differing pH values and the impacts on nosZ.
Keywords: nosZ; Clade II nosZ; Low pH; Nitrous oxide; N₂O; Nitrous oxide reducatse